Expression of the retinoblastoma protein RbAp48 in exocrine glands leads to Sjögren's syndrome–like autoimmune exocrinopathy - Ishimaru, Naozumi (The Rockefeller University Press, 2008)
Although several autoimmune diseases are known to develop in postmenopausal women, the mechanisms by which estrogen deficiency influences autoimmunity remain unclear. Recently, we found that retinoblastoma-associated protein 48 (RbAp48) induces tissue-specific apoptosis in the exocrine glands depending on the level of estrogen deficiency. In this study, we report that transgenic (Tg) expression of RbAp48 resulted in the development of autoimmune exocrinopathy resembling Sjögren's syndrome. CD4(+) T cell–mediated autoimmune lesions were aggravated with age, in association with autoantibody productions. Surprisingly, we obtained evidence that salivary and lacrimal epithelial cells can produce interferon-γ (IFN-γ) in addition to interleukin-18, which activates IFN regulatory factor-1 and class II transactivator. Indeed, autoimmune lesions in Rag2(−/−) mice were induced by the adoptive transfer of lymph node T cells from RbAp48-Tg mice. These results indicate a novel immunocompetent role of epithelial cells that can produce IFN-γ, resulting in loss of local tolerance before developing gender-based autoimmunity.